Power Functions and Their Relationship with the Unified Fractional Derivative - Manuel Duarte Ortigueira (Mathematics)
The different forms of power functions will be studied in connection with the unified fractional derivative, and their Fourier transform will be computed. In particular, one-sided, even, and odd powers will be studied.